Participatory design of an online greek language course - Zaphiris, Panayiotis; Zacharia, Giorgos (My University, 2001)
We present a design methodology for developing an online community supported Modern Greek language course. Participatory design was implemented as a four step spiral development process composed of (a) Building bridges with the intended users (b) Map user needs and suggestions to the system (c) Develop a prototype (d) Integrate feedback and continue the iteration. The approach followed in designing the course is presented and an evaluation of its success determined through the popularity of the course.